Ultrasound Imaging and Guidance in Common Wrist/Hand Pathologies - Mezian, Kamal; Ricci, Vincenzo; Jačisko, Jakub; Sobotová, Karolína; Angerová, Yvona; Naňka, Ondřej; Özçakar, Levent (American journal of physical medicine & rehabilitation, 2021)
Wrist/hand pain is a prevalent musculoskeletal condition with a great spectrum of etiologies (varying from overuse injuries to soft tissue tumors). Although most of the anatomical structures are quite superficial and easily evaluated during physical examination, for several reasons, the use of ultrasound imaging and guidance has gained an intriguing and paramount concern in the prompt management of relevant patients. In this aspect, the present review aims to illustrate detailed cadaveric wrist/hand anatomy to shed light into better understanding the corresponding ultrasonographic examinations/interventions in carpal tunnel syndrome, trigger finger, de Quervain tenosynovitis, rhizarthrosis, and the radiocarpal joint arthritis. In addition, evidence from the literature supporting the rationale why ultrasound guidance is henceforth unconditional in musculoskeletal practice is also exemplified.
Keywords: Ultrasonography, Interventional; Musculoskeletal Diseases; mrtvola; Cadaver; Hand; Musculoskeletal Pain; ruka; intervenční ultrasonografie; Ultrasonography; ultrasonografie; Humans; Wrist; lidé; muskuloskeletální bolest; muskuloskeletální nemoci; zápěstí